Zakah on shares: Theory and reality in Malaysia / Muhammad Ikhlas Rosele and Luqman Haji Abdullah - Rosele, Muhammad Ikhlas; Haji Abdullah, Luqman (Universiti Teknologi MARA Selangor, 2018)
Zakah (Islamic almsgiving) on shares are generally mentioned indirectly in classical fiqh books. This is due to the fact that the practice of shares is relatively new in classical Islamic jurisprudence literature. However, the basis of the debate on shares can be traced to its establishment and development in the classical fiqh discourse. Muslim individual and Muslim-operated companies have been involved in investment and share-trading, thus creating the debate of zakah on shares in Malaysia. Therefore, the objective of this study is to highlight the discussion of zakah on shares based on the reality in Malaysia. The focus of the debate will touch the aspects of legal shares, fiqh of zakah and its method of calculation.